PARADIGMA BARU KONSEP TA’WIL: Telaah atas Pemikiran Muhammad Syahrur - Deden Mula Saputra (Al-Dirayah, 2018)
This article is titled "The New Paradigm of the Concept of Ta'il: Review of Muhammad Syahrur's Thought. Muhammad Syahrur tried to make deconstruction as well as reconstruction of various concepts, theories and paradigms that had been established and became a mainstream understanding, thought, and even belief of the majority of Muslims. Especially through his effort entitled al-Kitab wa al-Qur'an: Mu'a asiraah Qira'ah. One of the deconstruction efforts carried out by Syahrur concerning the concept of ta'il as a methodology of understanding the Qur'anic text. The concept of ta'il referred to by Shahrur was introduced by the term manhaj at-tartil. An interesting thing to study is the deconstruction of the concept of ta'il which has been a sacred area in understanding the exoteric meaning of the Qur'an is understood differently by Syahrur. Then this article aims to find out how Muhammad Syahrur views the concept of ta'il and how the implications of applying the concept of ta'il are formulated by Muhammad Syahrur if used in tafsir of the Qur'an.